Biosynthesis of bacterial glycogen: primary structure of Salmonella typhimurium ADPglucose synthetase as deduced from the nucleotide sequence of the glgC gene. - Leung, P S (1987)
The nucleotide sequence of a 1.4-kilobase-pair fragment containing the Salmonella typhimurium LT2 glgC gene coding for ADPglucose synthetase was determined. The glgC structural gene contains 1,293 base pairs, having a coding capacity of 431 amino acids. The amino acid sequence deduced from the nucleotide sequence shows that the molecular weight of ADPglucose synthetase is 45,580. Previous results of the total amino acid composition analysis and amino acid sequencing (M. Lehmann and J. Preiss, J. Bacteriol. 143:120-127, 1980) of the first 27 amino acids from the N terminus agree with that deduced from nucleotide sequencing data. Comparison of the Escherichia coli K-12 and S. typhimurium LT2 ADPglucose synthetase shows that there is 80% homology in their nucleotide sequence and 90% homology in their deduced amino acid sequence. Moreover, the amino acid residues of the putative allosteric sites for the physiological activator fructose bisphosphate (amino acid residue 39) and inhibitor AMP (amino acid residue 114) are identical between the two enzymes. There is also extensive homology in the putative ADPglucose binding site. In both E. coli K-12 and S. typhimurium LT2, the first base of the translational start ATG of glgA overlaps with the third base TAA stop codon of the glgC gene.